PENETAPAN DAN PENERAPAN HARGA POKOK PENJUALAN SAPI PADA UD. RAJA FARM DI DESA SALAWAT KECAMATAN BATU KELIANG KABUPATEN LOMBOK TENGAH - Permadi, I Gusti Agung Didit Eka; Netrawati, I Gusti Ayu Oka; Oktiani, Asri; Putra, Bagus Oka Mahadi; Maulana, L. Gede Ahmad Yuna Niza (Devote: Jurnal Pengabdian Masyarakat Global, 2023)
This community service activity aims to provide training in the form of a simulation of the calculation of the cost of goods sold which is the basis for determining the selling price of cattle to farmers at UD. Raja Farm. The conclusion obtained from this community service activity is that this activity takes place within one day which begins with a basic and systematic explanation of the method of determining the selling price with a full costing approach. Suggestions that can be given by the Community Service Team to UD. Raja Farm that the determination of the selling price of cattle must be calculated based on the cost of goods sold because the costs during maintenance can be identified with a full costing approach so that it can determine the appropriate selling price so that cattle farmers can get greater profits.